2014
DOI: 10.1007/s10551-014-2311-8
|View full text |Cite
|
Sign up to set email alerts
|

Humility in Management

Abstract: Although virtues have gained a firm presence in the theory and practice of corporate management, humility is not ranked as one the chief virtues in the business world. In spite of this, it is an important virtue, contributing to the manager's moral and professional quality and the development of the company's human team. This paper explains the basic traits of humility in general and how they manifest in the manager's life and profession, and shows, within the ethics of virtues, that it is not just a personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
121
1
21

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(144 citation statements)
references
References 32 publications
1
121
1
21
Order By: Relevance
“…example, accurate self-knowledge can be manifested intrapersonally as an internal willingness and means for self-improvement as well as interpersonally as a way of relating to others (see Argandona 2015). In contrast, other components appear isolated or narrowly focused or reflect the 'lack of' elements that, as noted previously, may be inappropriate (Tangney 2000).…”
Section: Theorized Key Components Of Humility: Synthesizing Prior Workmentioning
confidence: 94%
“…example, accurate self-knowledge can be manifested intrapersonally as an internal willingness and means for self-improvement as well as interpersonally as a way of relating to others (see Argandona 2015). In contrast, other components appear isolated or narrowly focused or reflect the 'lack of' elements that, as noted previously, may be inappropriate (Tangney 2000).…”
Section: Theorized Key Components Of Humility: Synthesizing Prior Workmentioning
confidence: 94%
“…Scholars of business ethics suggested that organizational structures enable resistance to narcissism (Godkin and Allcorn 2011). To inhibit downward spirals between narcissistic leadership, amoral emotions, and unethical behavior, we recommend that organizations adjust their hiring and promotion practices (Lubit 2002), hold leaders accountable to organizational fair-play rules (Ouimet 2010), foster self-awareness and humility in management (Argandona 2015), and monitor deviant behaviors (Grijalva and Harms 2014).…”
Section: Contributionsmentioning
confidence: 99%
“…A growing number of scholars have argued that leader humility is important to organizational/team effectiveness (Argandoña 2014;Owens and Hekman 2012;Vera and Rodriguez-Lopez 2004;Weick 2001). In the modern organizational context characterized by high complexity and requirements for adaptability (Goddard and Eccles 2013;Weick 2001), a greater emphasis on the bottom-up aspects of leadership is necessary.…”
Section: Perceived Impact Of Leaders' Humility On Team Effectivenessmentioning
confidence: 99%
“…Over the last years, however, such negative perspectives of humility have been changing. The significance of humble leadership has attracted more and more interest in recent years, mainly in the wake of corporate scandals attributed to the hubris, narcissism and arrogance of corporate executives (Argandoña 2014;Boje et al 2004;Hühn 2014;Owens and Hekman 2012). The Economist (2013, p. 59) reasoned that "arrogance breeds mistakes" and that "If leadership has a secret sauce, it may well be humility".…”
Section: Introductionmentioning
confidence: 99%